Controlled Release Mechanism and Antibacterial Effect of Layer‐By‐Layer Self‐Assembly Thyme Oil Microcapsule. Issue 6 (9th May 2019) - Zhang, Zhao; Zhang, Shanshan; Su, Rongrong; Xiong, Die; Feng, Wu; Chen, Jiaping
Abstract : Abstract: Thyme essential oil‐loaded microcapsules (TMS) were fabricated using natural polysaccharide chitosan (CS) and sodium alginate (SA) as the shell material via the method of layer‐by‐layer (LBL) assembly. The accumulated release rates of thyme oil and microcapsules at 4 °C were 42.50% and 10.16%, respectively. After heating at 100 °C for 5 hr, the release rate of the 0, 2, 4, 6 layers assembled microcapsules were 100%, 48.84%, 28.38%, 19.3%, severally. Microcapsules also had good pH sensitivity in the range of 4 to 10. Antimicrobial function studies showed that the microcapsules are more effective than thyme oil for three tested microorganisms. When the temperature rose from 37 °C to 121 °C, the antibacterial zone of thyme oil gradually decreased from 18.5 ± 0.6 mm to 12.3 ± 0.6 mm, although inhibition rate of microcapsules increased from 87.97% to 99.75%. The antibacterial effect of thyme oil declined with the increase of pH, in terms of microcapsules, the efficiency was better under acidic or alkaline conditions. The thyme oil microcapsules can suppress the growth of Staphylococcus aureus in milk and prolong its shelf life. It was determined that this microcapsule could be a potential alternative as a natural antimicrobial agent in food and pharmaceutical industries. Practical Application: This work provided release performance and mechanism of layer‐by‐layer (LBL) thyme oil microcapsule under different conditions, and further studies showed its antibacterial ability to explore how herb essential oils can be potentially applied in food packaging and antibacterial areas.